Application of Rice Field Snails (Pila ampullacea) Extract as an Alternative Substitute for Protein Sources in Export-Quality Catfish Feed (Clarias sp.) - Kasim, Syahruddin; Hala, Yusafir; Sri Rahayu, Lulu (Indonesian Journal of Chemical Research, 2023)
The freshwater fishery commodity that ranks at the top in total production in Indonesia, and its high domestic consumption, is catfish (Clarias sp.). One of the efforts to provide alternative feeds is by using rice field snails (Pila ampullacea) due to their high protein content. This study aims to determine the content of P. ampullacea feed and its application as an alternative protein source in export-quality Clarias sp. The feed was prepared by combining P.ampullacea flour, rice bran, and corn flour in a ratio of 3:1:1. Analysis of water content was conducted using the weight reduction method, ash content using the ashing method, protein content using the Kjeldahl method, and fat content using the soxhletation method. The analysis results showed that P. ampullacea had water content of 7.97%, ash content of 10.36%, protein content of 50.17%, and fat content of 4.16%. Meanwhile, the P.ampullacea feed had water content of 10.49%, ash content of 8.26%, protein content of 48.74%, and fat content of 3.6%. The results indicated that the application of P.ampullacea to Clarias sp. led to an increase in protein and fat content every week, the levels found in the commercial feed used.